Negative Impoliteness Strategy Found in “No Nose Knows” Episode: A Pragmatic Point of View - Ida Komang Ambarani; Ni Made Diana Erfiani; Yohanes Octovianus L. Awololon (Universitas Negeri Makassar, 2026)
Abstract. No Nose Knows episode is crucial to be analysed since it contains a lot of verbal expressions and conflicts which reflect to negative impoliteness strategy to damage someone’s negative face. This study aims to analyze negative impoliteness among the characters in No Nose Knows episode of SpongeBob SquarePants and its factors caused. Descriptive qualitative was used to describe the data comprehensively. In this frame, the data were collected by applying content analysis and notetaking from the video website with the researcher be the primary instrument because of being responsible for collecting, transcribing, and analysing the data. Creswell’s Framework (2013) was used to present the data which include preparing and organizing data, reducing data, then representing the data in the form of discussion. The results found that negative impoliteness conveyed through condescend, scorn, and ridicule, invade the other face, and associating someone with a negative aspect explicitly. Additionally, speakers’ intention in damaging someone’s face, different social power, also the intimate relationship are the factors behind those strategies. This study contributes to pragmatics studies by demonstrating the way negative impoliteness is strategically employed in animated movie to construct interpersonal conflict and social hierarchy among characters. The findings may help pepople to understand the way negative impoliteness and its factors operate in everyday interactions. Keywords: Negative Impoliteness, Pragmatics, SpongeBob SquarePants